Pengaruh Display Produk, Store Atmosphere, dan Keterlibatan Media Sosial terhadap Keputusan Pembelian Produk Kosmetik Emina Pada Mahasiswi NTT Manggarai Barat di Yogyakarta - Magdalena Stevani Nova; Heri Prasetyo (CV Muara Edukasi, 2026)
This study aims to analyze the influence of product display, store atmosphere, and social media engagement on the purchase decisions of Emina cosmetic products among female university students from East Nusa Tenggara (NTT), particularly West Manggarai Regency, studying in Yogyakarta. This research uses a quantitative approach with an explanatory research method. The sample consisted of 150 respondents selected through purposive sampling. Data were collected using a Likert-scale questionnaire and analyzed using multiple linear regression with the assistance of IBM SPSS Statistics 27. The results indicate that product display, store atmosphere, and social media engagement have a positive and significant effect on purchase decisions. Store atmosphere is the most dominant variable with a standardized beta value of 0.302. Simultaneously, the three variables significantly influence purchase decisions, with an R Square value of 0.524, indicating that they explain 52.4% of the variation in purchase decisions. This study highlights the importance of integrating physical store strategies and social media engagement to strengthen young consumers’ purchase decisions